Accumulation of large very low density lipoprotein in plasma during intravenous infusion of a chylomicron-like triglyceride emulsion reflects competition for a common lipolytic pathway. - Bjorkegren, J; Packard, C; Hamsten, A; Bedford, D; Caslake, M; Foster, L; Shepherd, J; Stewart, P; Karpe, F (1996)
Very low density lipoproteins (VLDL) are produced in the liver and contain apolipoprotein (apo) B-100 and endogenous lipids. By contrast, ingestion of fat leads to formation of chylomicrons containing apoB-48 secreted from the intestine. In this study, a 60-min intravenous infusion of a chylomicron-like triglyceride emulsion was given to healthy young men to examine whether competition between chylomicrons and VLDL for the same lipolytic pathway explains the increase in VLDL seen after meals. The responses of two major VLDL subfractions were determined by measuring the concentrations of apoB-100 in fractions of triglyceride-rich lipoproteins with Svedberg flotation rates of 60-400 (large VLDL) and 20-60 (small VLDL) that were separated from plasma by density gradient ultracentrifugation. A threefold elevation in plasma triglycerides was observed during the infusion together with a consistent linear increase of large VLDL. The rate at which large VLDL accumulated in plasma differed markedly among individuals and was not enhanced by doubling of the infusion rate. The response of small VLDL was more heterogeneous; however, a decrease was seen in most subjects. The combined pattern for the two VLDL species is what would be expected if large VLDL particles are the precursors of smaller VLDL species and if lipolysis of large VLDL is inhibited through competition from the triglyceride emulsion. The extent to which the triglyceride emulsion inhibited the lipolysis of VLDL and/or influenced the synthesis rate of large VLDL was estimated from simultaneous stable isotope studies. The emulsion caused a 75-90% block of the conversion of large VLDL apoB to small VLDL apoB and there was no sign of enhanced synthesis of large VLDL after infusion of the triglyceride emulsion. The corollary of these findings is that chylomicrons and their remnants impede the normal lipolytic degradation of VLDL and could thereby be indirectly implicated in the generation of atherogenic remnant lipoproteins.